PENGELOLAAN MENU GLUTEN DI RESTAURANT PANGERAN BEACH HOTEL PADANG - Zuliyana, Devi; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Indonesia has great potential in the tourism sector. Tourism is an important sector in supporting very fast economic growth and providing job opportunities. We can see that its natural resources, national culture and history, unique festivals and ceremonies attract tourists. This research aims to find out the types of food ingredients included in the gluten menu and to find out how to manage the gluten menu at the Pangeran Beach Padang restaurant. In managing the gluten menu there are several steps including planning, organization, implementation, monitoring and evaluation. This type of research uses a qualitative method with a descriptive approach to describe and explain the situation that occurred by collecting field data and information. The key informant in this research is Cook. Meanwhile, data collection techniques in this research used interviews, observation and documentation. Based on the results of research that has been carried out, so far the management of the gluten menu is quite good, although there are several things that influence the process of managing the gluten menu. By taking steps to manage the gluten menu, you can improve the quality of the menu and provide the best presentation. To know the steps for managing gluten menus in restaurants can ensure consistency, safety, efficiency and quality in carrying out tasks for the gluten menu management process. The research provides suggestions and hopes for hotels to be able to maintain and increase employee comfort by providing facilities for employees. Keywords: Gluten, Menu, Hotel, Restaurant